Britas graduadas simples: influência da litologia, estrutura interna e umidade na deformabilidade - Sagrilo, Amanda Vielmo (2024)
The granular base of asphalt pavements has a dual function of providing support for the surface layer and for allowing the water to exit from the structure. This layer suffers the effects of flooding, due to precipitation or capillarity from the subgrade, and drying, due to seasonality or drainage, so that throughout the service, life there is some variability in the material's humidity. However, the laboratory determination of the resilience modulus and permanent deformation occurs recurrently only at the optimum moisture content. This study evaluated unbound granular materials from two different lithological types, rhyodacite and syenogranite, regarding stiffness and permanent deformation in flooded and dry situations. To this end, the rocks were characterized by petrographic analysis and elastic dynamic modulus mechanical, physical and shape characterization of the aggregates, characterization of unbound granular materials by sieve analysis tests, compaction, suction, in addition to the main deformability tests, as resilience modulus and permanent deformation for dry, optimal and flooded conditions. Mechanistic analysis and computed tomography of compacted samples were also performed. The main results indicate that the characteristics of the parent rock are inherited by the aggregates and affect the properties of the unbound granular materials. such as mechanical performance and porosity. Dry tests showed high stiffness and low permanent deformation, due to matric suction effects. At optimal moisture content, the deformability between the two lithological types was similar, whereas in the flooded tests, the absorption of the aggregates plays an important role as, depending on the material's affinity with water, drainage is easier, affecting the deformations. The mechanistic analysis highlighted the importance of subgrade stiffness in design, especially for rutting. The structures that used dry bases had lower rutting and contributed to less fatigue cracking of the asphalt layer, while the flooded structures had greater accumulation of deformations, especially in less rigid subgrades. Computed tomography analysis made it possible to qualitatively evaluate the contacts between grains, the patterns of aggregate breakage, the distribution of pores and their characteristics. In a quantitative analysis, it was possible to confirm the higher porosity at the extremities of the samples, in addition to characterizing the pores. Isolated pores are, in general, low-volume isotropic spherical pores. The connected pores are larger and oriented. There is also variation between the two lithologies, in agreement with other tests.